2021
DOI: 10.1111/jce.15028
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of clinical success after paroxysmal atrial fibrillation catheter ablation

Abstract: Introduction Contact force (CF) guided ablation of paroxysmal atrial fibrillation (PAF) with stable catheter‐tissue contact optimizes clinical success and may increase an operator's ability to achieve pulmonary vein isolation (PVI) in a single encirclement. First pass PVI reduces procedure time but the relationship with long term clinical success is not well understood. This study evaluated patient characteristics and procedural details as predictors of 1‐year clinical success after PAF ablation, including fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…Osorio et al reported that first-pass isolation on at least one side was an independent predictor of atrial tachyarrhythmia recurrence-free survival after PVI. 20 However, Osorio et al also showed that first-pass isolation on both sides, which was generally used as first-pass isolation, was not a predictor of atrial tachyarrhythmia recurrence-free survival. 20 In the present study, the recurrence-free survival rate was similar between patients with and without first-pass isolation on both sides.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Osorio et al reported that first-pass isolation on at least one side was an independent predictor of atrial tachyarrhythmia recurrence-free survival after PVI. 20 However, Osorio et al also showed that first-pass isolation on both sides, which was generally used as first-pass isolation, was not a predictor of atrial tachyarrhythmia recurrence-free survival. 20 In the present study, the recurrence-free survival rate was similar between patients with and without first-pass isolation on both sides.…”
Section: Discussionmentioning
confidence: 99%
“… 20 However, Osorio et al also showed that first-pass isolation on both sides, which was generally used as first-pass isolation, was not a predictor of atrial tachyarrhythmia recurrence-free survival. 20 In the present study, the recurrence-free survival rate was similar between patients with and without first-pass isolation on both sides. Wang et al estimated the impact of moderate AI targets (i.e., LA anterior wall 400–450, posterior wall 280–330, and roof/inferior wall 380–430) on the outcomes of PVI in 140 patients with paroxysmal AF and reported low rates of first-pass isolation (49.3%) and excellent recurrence-free survival at the 1-year follow-up (92.1%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FPI is an excellent acute indicator of the quality of RF PVI, and it serves as a reliable surrogate for long‐term success rates 6 . As such it is notable that the reported FPI rates with vHPvSD have been modest, ranging from 18% to 61% 4,5,7 (Table 1).…”
Section: Efficacy Of Vhpvsd Ablationmentioning
confidence: 99%
“…We hypothesised that using a novel, modified CLOSE protocol proper isolation of the PVs is achievable even in patients with larger LAWT. First-pass isolation is a valuable marker of PVI's acute procedural success [15,16]. The effects of PV anatomy and LAWT on successful first-pass isolation has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%